Mango Fruit Fly, Ceratitis cosyra (Walker) (Insecta: Diptera: Tephritidae) - Gary J. Steck (EDIS)
The mango fruit fly is also commonly known as the marula fruit fly, based on its common occurrence in these host plants. Marula is a native African fruit related to mango and sometimes known locally as wild plum. This fly is a serious pest in smallholder and commercial mango across sub-Saharan Africa, where it is more destructive than either the Mediterranean fruit fly or the Natal fruit fly. The fly’s impact is growing along with the more widespread commercialization of mango. It is one of the most commonly intercepted fruit flies in Europe. This 3-page fact sheet was written by G. J. Steck, and published by the UF Department of Entomology and Nematology, March 2012.